Analysis of Functional Positions and Professionalism of Civil Servants in Buton Utara Regency - Sulimin, Muhammad; Amir, Muh.; Erowati, Dewi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Team member' professionalism is determined by their ability to carry out tasks according to their field and level. This study aims to analyze the appointment of functional positions in Buton Utara Regency in improving team member professionalism. Using a qualitative approach, data was obtained through in-depth interviews and documentation from functional officials and local community leaders. The analysis used reduction, presentation, and conclusion-drawing techniques. The study results indicate that appointing functional positions in Buton Utara is by central government procedures and can improve team members' professionalism. The ASN Law emphasizes the importance of competence as the foundation of the ASN profession. Appointment is carried out by recruiting civil servants or transfers from other positions. Efforts to improve professionalism involve education and training, with supporting factors such as work performance, skills, knowledge, and rank levels and inhibiting factors such as low competence and inappropriate attitudes.